Accelerated Stability Study of Gojihvadi Kwath Granules - Sharma, Dr. Khemchand (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACT Saviryata avadhi (shelf life) of Ayurvedic preparations is a burning problem specifically with Panchvidha Kashaya Kalpana (Primary preparations) apart from their difficult handling; poor palatability and odour etc. Gojihvadi kwath is one such preparation which is widely used in the treatment of fever. Saviryata avadhi (Self life) of kwath preparation is merely one day as mentioned in our classical texts and it has been reported that conversion of kwath into granules can accelerates its shelf life upto one year. So, in the present study fabrication of Gojihvadi Kwath into granules was done and the dosage form so obtained was trialed for accelerated stability study upto 6 month using organoleptic characters as well as physico chemical parameters mentioned in Ayurvedic pharmacopeia including microbial contamination. The results of this study showed no marked changes in organoleptic as well as in physico chemical parameters indicating accelerated shelf life of granules over kwath preparation up to a period of six months. Thus it proves that shelf life of Gojihvadi Kwath can be increased upto one year in Granules form.